2020
DOI: 10.1155/2020/8607418
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End Products Induce Proliferation and Migration of Human Aortic Smooth Muscle Cells through PI3K/AKT Pathway

Abstract: Advanced glycation end products (AGEs) have been widely regarded as an important inducing factor in the pathogenesis of diabetic arteriosclerosis, and the proliferation and migration of vascular smooth muscle cells (VSMCs) are also involved in this process. However, it is not clear whether AGEs promote atherosclerosis by inducing the proliferation and migration of VSMCs. To figure out this question, this study investigated the effects of AGEs on the proliferation and migration of human aorta vascular smooth mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The interaction of advanced glycation end products (AGEs) and receptor of advanced glycation end product (RAGE) ( Figure 3 ) in the vascular system of diabetic patients activates downstream PI3K/AKT pathways, thereby promoting human aorta VSMC proliferation and migration. Consequently, inhibition of the PI3K/AKT pathway may become a new strategy for the treatment of diabetic atherosclerosis ( Yuan et al, 2020 ). Rosiglitazone ( Figure 3 ) has been reported to inhibit insulin-stimulated VSMC proliferation by inhibiting the PI3K/Akt/mTOR/P70S6K cascades ( Park et al, 2008 ).…”
Section: Pi3k-targeted Therapy In Atherosclerosismentioning
confidence: 99%
“…The interaction of advanced glycation end products (AGEs) and receptor of advanced glycation end product (RAGE) ( Figure 3 ) in the vascular system of diabetic patients activates downstream PI3K/AKT pathways, thereby promoting human aorta VSMC proliferation and migration. Consequently, inhibition of the PI3K/AKT pathway may become a new strategy for the treatment of diabetic atherosclerosis ( Yuan et al, 2020 ). Rosiglitazone ( Figure 3 ) has been reported to inhibit insulin-stimulated VSMC proliferation by inhibiting the PI3K/Akt/mTOR/P70S6K cascades ( Park et al, 2008 ).…”
Section: Pi3k-targeted Therapy In Atherosclerosismentioning
confidence: 99%
“…As demonstrated in Figure 1A , the administration of AGEs induced Ca 2+ deposition (black deposits) in our cellular model in a dose-dependent manner, within the range of 25 mg/L to 100 mg/L compared to no AGEs treatment. The concentrations used were based on the preliminary experiments ( Yuan et al, 2020 ) that stimulate calcification in HVSMC in a dose-dependent manner in vitro ( Kay et al, 2016 ). Sayo Koike's study produced the same results ( Koike et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Supplementary to these previous findings, the current study further showed that AGEs upregulated the expression of K17 and resulted in the nuclear export and degradation of p27 KIP1 , leading to progressed cell cycle and ultimately the proliferation of keratinocytes. Multiple studies have demonstrated the pro-proliferative effects of AGEs on different types of cells like mesangial cells and aortic smooth muscle cells [25][26][27]. However, some other studies have claimed the inhibitory effects of AGEs on cell proliferation or cell cycle progression in ovarian granulosa cells and intestinal epithelial cells [58,59].…”
Section: Discussionmentioning
confidence: 99%